Identification of CCR7 and CBX6 as key biomarkers in abdominal aortic aneurysm: Insights from multi‐omics data and machine learning analysis - Xi Yong; Xuerui Hu; Tengyao Kang; Yanpiao Deng; Sixuan Li; Shuihan Yu; Yani Hou; Jin You; Xiaohe Dai; Jialin Zhang; Junjia Zhang; Junlin Zhou; et al. (IET Systems Biology)
Abstract Abdominal aortic aneurysm (AAA) is a severe vascular condition, marked by the progressive dilation of the abdominal aorta, leading to rupture if untreated. The objective of this study was to identify key biomarkers and decipher the immune mechanisms underlying AAA utilising multi‐omics data analysis and machine learning techniques. Single‐cell RNA sequencing disclosed a heightened presence of macrophages and CD8‐positive alpha‐beta T cells in AAA, highlighting their critical role in disease pathogenesis. Analysis of cell–cell communication highlighted augmented interactions between macrophages and dendritic cells derived from monocytes. Enrichment analysis of differential expression gene indicated substantial involvement of immune and metabolic pathways in AAA pathogenesis. Machine learning techniques identified CCR7 and CBX6 as key candidate biomarkers. In AAA, CCR7 expression is upregulated, whereas CBX6 expression is downregulated, both showing significant correlations with immune cell infiltration. These findings provide valuable insights into the molecular mechanisms underlying AAA and suggest potential biomarkers for diagnosis and therapeutic intervention.